Additives and metal manufacturing methods
The use of quinone oligomers in liquid-phase synthesis suppresses necking and coarsening of metal particles, enabling uniform deposition and production of fine metal particles for electronic components.
Patent Information
- Application Number
- JP2023020787
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-02-14
- Publication Date
- 2025-11-06
- Estimated Expiration
- 2043-02-14
AI Technical Summary
Conductive particles used in electronic pastes neck together and become coarse during metal deposition, making them difficult to use due to strong aggregation and bonding, especially with smaller particle sizes.
Incorporating a quinone oligomer additive in the liquid-phase synthesis process to suppress necking and coarsening of metal particles by forming a complex with transition metals, using pyrolysis GC-MS and MALDI-TOF/MS to characterize the oligomer, and employing a method that includes a metal deposition step with controlled quinone oligomer concentration.
The quinone oligomer effectively prevents necking and coarsening of metal particles, allowing for uniform deposition and production of fine metal particles suitable for electronic components.
Smart Images

Figure 0007765423000005 
Figure 0007765423000006 
Figure 0007765423000007
Abstract
Description
[Technical Field]
[0001] The present invention relates to an additive used in liquid phase synthesis for depositing metals, and a method for producing metals using the additive. [Background technology]
[0002] As electronic components become smaller and electrodes become thinner, smaller particle diameters and sharper particle size distributions are required for core-shell metal powders in electronic pastes. For example, Patent Document 1 and Non-Patent Documents 1 and 2 disclose technologies related to conductive particles. Non-Patent Document 3 also discloses a technology for synthesizing fine particles using polyvinylpyrrolidone (PVP) as a protective agent. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Japanese Patent Application Laid-Open No. 2010-238419 [Non-patent literature]
[0004] [Non-Patent Document 1] Daisuke Shimamoto, Masashi Hattori, Hiroki Ago, Masaharu Tsuji, Abstract of the 9th Symposium on Molecular Science, 2P077, published August 31, 2015 [Non-patent document 2] Nature nanotechnology, 6, 302 (2011) Supplementary information [Non-patent document 3] Bin Zhao, Naoki Toshima, Polymer Proceedings Vol. 46 (1989) No. 9 pp. 551 Summary of the Invention [Problem to be solved by the invention]
[0005] However, the smaller the particle size of conductive particles, the more likely they are to neck together and become coarse during the metal deposition process using liquid-phase synthesis (electroless plating). Furthermore, this aggregation and bonding (necking) can be so strong that it cannot be broken down, making it difficult to use as a conductive powder.
[0006] Therefore, a primary object of the present disclosure is to provide an additive that suppresses necking and coarsening of the metal produced during metal precipitation by liquid phase synthesis. Another object is to provide a method for depositing (producing) a metal using the additive. [Means for solving the problem]
[0007] The additive disclosed herein is characterized by containing a quinone oligomer. The additive disclosed herein is used in liquid-phase synthesis for precipitating a metal from a solution containing a metal ion and / or a metal complex.
[0008] By precipitating metal from metal ions and / or metal complexes in the presence of quinone oligomers, necking between the precipitated metal particles and coarsening of the metal particles are suppressed.
[0009] In one embodiment of the additive disclosed herein, the additive can be used when the metal to be deposited is a transition metal. Because the quinone oligomer and the transition metal easily form a complex, necking between the deposited transition metal particles and coarsening of the metal are suitably suppressed.
[0010] In one embodiment of the additive disclosed herein, the quinone oligomer has the following characteristics (1) and (2): (1) Hydroquinone is detected by pyrolysis GC-MS; (2) At least one peak is detected within the m / z range of 200 to 1200 by MALDI-TOF / MS; This more suitably suppresses necking between the precipitated metal particles and coarsening of the metal.
[0011] In one embodiment of the additive disclosed herein, in the results of MALDI-TOF / MS measurement of the quinone oligomer, the peak area in the m / z range of 200 to 1200 accounts for 50% or more of the total peak area, which more suitably suppresses necking between precipitated metal particles and coarsening of the metal.
[0012] The present disclosure also provides a method for producing a metal (precipitation method). The method for producing a metal disclosed herein includes precipitating the metal from a solution containing metal ions and / or a metal complex and a quinone oligomer. This allows for the production of a metal (e.g., in the form of particles or a film) in which necking and coarsening are suppressed.
[0013] In one embodiment of the method for producing a metal disclosed herein, the concentration of the quinone oligomer in the solution is 0.02 g / L or more and 200 g / L or less, which makes it possible to suitably suppress necking and coarsening of the produced metal. [Brief explanation of the drawings]
[0014] [Figure 1] FIG. 1 is a peak diagram showing the measurement results of pyrolysis GC-MS (pyrolysis temperature: 300° C.) of a quinone oligomer. [Figure 2] FIG. 1 is a peak diagram showing the measurement results of pyrolysis GC-MS (pyrolysis temperature: 600° C.) of a quinone oligomer. [Figure 3] 1 shows the results of MALDI-TOF / MS measurement of quinone oligomers (peak diagram with m / z values ranging from 10 to 1500). [Figure 4] FIG. 4 is an enlarged view of the range of m / z values from 10 to 300 in the MALDI-TOF / MS measurement results shown in FIG. [Figure 5] 1 is a TEM-EDX analysis image (magnification: 100,000 times) of the powder material in Example 1. [Figure 6] 1 is a TEM-EDX analysis image (magnification: 1,000,000 times) of the powder material in Example 1. [Figure 7]1 is an image (magnification: 20,000 times) of an FE-SEM-EDX analysis of a powder material in Comparative Example 1. [Figure 8] 1 is a TEM-EDX analysis image (magnification: 100,000 times) of the powder material in Example 2. [Figure 9] 1 is a TEM-EDX analysis image (magnification: 1,000,000 times) of the powder material in Example 2. [Figure 10] 1 is an image (magnification: 20,000 times) of an FE-SEM-EDX analysis of a powder material in Comparative Example 2. [Figure 11] 10 is a backscattered electron image of a powder material in Example 3, taken by FE-SEM. [Figure 12] 10 is a backscattered electron image of the powder material in Example 4 taken by FE-SEM. [Figure 13] 10 is a backscattered electron image of a powder material in Comparative Example 3, taken by FE-SEM. DETAILED DESCRIPTION OF THE INVENTION
[0015] An embodiment of the present technology will be described below. Matters other than those specifically mentioned in this specification that are necessary for implementing the present technology can be understood as design matters for a person skilled in the art based on the prior art in the relevant field. The present technology can be implemented based on the contents disclosed in this specification and the technical common sense in the relevant field. In this specification, when a numerical range is described as "A to B (where A and B are arbitrary numerical values)," this means "A or more and B or less," and also encompasses the meanings of "greater than A and less than B," "greater than A and B or less," and "greater than A and less than B."
[0016] The additive disclosed herein contains at least a quinone oligomer. The additive disclosed herein is suitably used as an additive in a metal precipitation reaction in liquid-phase synthesis. Metal precipitation in liquid-phase synthesis is, for example, by reduction of metal ions and / or metal complexes. The quinone oligomer present in the solution suitably controls the metal precipitation behavior and suppresses necking and coarsening of the precipitated metal.
[0017] As used herein, the term "quinone oligomer" refers to a polymer formed by the bonding of multiple quinone-containing monomers. While the composition and structure of the quinone oligomer are not particularly limited, examples of monomers constituting the quinone oligomer include hydroquinone (HQ) and benzoquinone (BQ). For example, a preferred example of the quinone oligomer contained in the additive disclosed herein may be a quinone oligomer containing at least hydroquinone as a monomer and having a molecular weight of 200 or more. The inclusion of hydroquinone in the quinone oligomer increases the number of OH groups possessed by the quinone oligomer, making it more soluble in water and facilitating its use in aqueous solvents. In addition, as used herein, the term "oligomer" refers to a polymer formed by the polymerization of at least two monomers (e.g., a dimer to a hexamer), with no particular upper limit (i.e., including polymers). Furthermore, the quinone oligomer does not necessarily have a single composition or structure and may be a mixture.
[0018] For quinone oligomers, a peak derived from hydroquinone is preferably detected by pyrolysis GC-MS at 600°C. Benzoquinone can also be detected by pyrolysis GC-MS at 600°C. If the results obtained by pyrolysis GC-MS at 600°C are complicated and difficult to analyze, a double shot analysis can be performed in which the sample is heated once to 300°C and then to 600°C, and the analysis is carried out in two stages. In this case, it is preferable that hydroquinone is detected at either temperature. Benzoquinone can also be detected at either temperature.
[0019] When quinone oligomers are subjected to pyrolysis GC-MS, impurities that may be mixed in during the synthesis of the quinone oligomers and pyrolysis products derived from the quinone oligomers can be detected. For example, pyrolysis GC-MS at 600°C can detect ethanol, propanol, acetic acid, phenol, etc. Since phenol has a benzene ring, it is presumed to be derived from the quinone that constitutes the quinone oligomers. Furthermore, pyrolysis GC-MS at 300°C can detect, for example, hydroquinone, acetic acid, 2-furanone, maleimide, 4-methyl-3-penten-2-one, etc.
[0020] The proportion of quinone-containing monomers among the monomers constituting the quinone oligomer may be 50% or more, and may be 60% or more, 70% or more, 80% or more, 90% or more, or 100%.
[0021] In a peak diagram obtained by analyzing a quinone oligomer by MALDI-TOF / MS, it is preferable that the quinone oligomer has at least one peak in the m / z range of 200 to 1200, and preferably has at least one peak in the m / z range of 200 to 1000, 200 to 700, 250 to 750, or 250 to 500. This allows for favorable control of the metal deposition behavior.
[0022] Furthermore, in a peak diagram obtained by analyzing the quinone oligomer by MALDI-TOF / MS, it is preferable that the quinone oligomer has a peak group consisting of 3 or more, preferably 5 or more, and more preferably 10 or more peaks in the m / z range of 200 to 1200. It is also preferable that the quinone oligomer has a peak group consisting of 3 or more, preferably 5 or more, and more preferably 10 or more peaks in the m / z range of 200 to 1000. It is also preferable that the quinone oligomer has a peak group consisting of 3 or more, preferably 5 or more, and more preferably 10 or more peaks in the m / z range of 200 to 700. It is also preferable that the quinone oligomer has a peak group consisting of 3 or more, preferably 5 or more, and more preferably 10 or more peaks in the m / z range of 250 to 500. These characteristics indicate that the quinone oligomer has a complex branched structure and is a mixture of substances with various molecular weights and structures, making it possible to respond to various metal precipitation reactions. Furthermore, because the quinone oligomer has a branched structure, it is more likely to gel during the metal precipitation reaction, and as described below, the adhesion of organic matter derived from this quinone oligomer to the surface of the generated metal suppresses necking and coarsening between the metals.
[0023] Furthermore, in a peak diagram obtained by analyzing a quinone oligomer by MALDI-TOF / MS, the sum of peak intensities in the m / z range of 200 to 1200 preferably accounts for 50% or more of the total peak intensity, more preferably 60% or more, and even more preferably 70% or more. This means that the quinone oligomer is estimated to contain little unreacted monomer or impurities that may be generated during the synthesis of the quinone oligomer, and therefore the quinone oligomer's effect of suppressing necking and coarsening of metals is more suitably exhibited.
[0024] The additive disclosed herein may contain the quinone oligomer as a solid or dissolved in an appropriate solvent. When the additive contains the quinone oligomer as a solid, its shape is not particularly limited and may be, for example, powder, granules, blocks, cotton, or the like. When the additive contains a solid quinone oligomer, the quinone oligomer dissolves when mixed with a solvent, and the quinone oligomer can be supplied in a dissolved state during liquid-phase synthesis. When the quinone oligomer contained in the additive is dissolved, it is preferable to use, for example, an aqueous solvent as the solvent. Aqueous solvents easily dissolve quinone oligomers. Examples of aqueous solvents include water (e.g., pure water, deionized water, etc.) and mixtures mainly containing water (e.g., a mixture of water and a lower alcohol).
[0025] The method for synthesizing the quinone oligomer is not particularly limited, and the quinone oligomer can be synthesized by referring to, for example, Polymer Science USSR Vol. 24 No. 10 pp. 2434-2440, 1982. An example of the method for synthesizing the quinone oligomer is shown in the test example described later.
[0026] The additive disclosed herein may contain, in addition to the quinone oligomer, other additives, such as a pH adjuster, a protective agent, a dispersant, a complexing agent, a reducing agent, etc.
[0027] A method for producing (precipitating) a metal using the additive disclosed herein is described below. The method for producing a metal disclosed herein includes precipitating the metal from a solution containing metal ions and / or a metal complex and a quinone oligomer.
[0028] In the following description, a method for depositing a metal on a substrate will be described as an example. Note that a substrate is not essential in this technology. If no substrate is used, the deposited metal is deposited in a solution. When a substrate is used, the type of substrate is not particularly limited, and may be, for example, metal particles, metal members, ceramic particles, ceramic members, etc. In the following example, a case where ceramic particles are used as the substrate will be described. Note that a manufacturing example in which a substrate is not used can be understood by omitting the substrate from the following description.
[0029] The method for producing a metal disclosed herein includes a metal deposition step of depositing the metal from a solution containing metal ions and / or metal complexes and a quinone oligomer. The method disclosed herein may also include a material preparation step prior to the metal deposition step. Each step will be described in detail below.
[0030] (1) Material preparation process The material preparation step includes preparing a solution in which the metal to be deposited is dissolved (hereinafter also referred to as a "metal deposition solution.") In this embodiment, ceramic particles are prepared as the base material.
[0031] The metal deposition solution contains a quinone oligomer and a metal to be deposited. The metal to be deposited is preferably present in a dissolved state in a solvent, for example, in the form of a metal ion or a metal complex. For example, the metal to be deposited can be contained in the metal deposition solution by dissolving a metal compound containing the metal in a solvent. Metal salts, complexes, and the like can be preferably used as such metal compounds. Examples of salts include halides such as chlorides, bromides, and iodides, hydroxides, sulfides, sulfates, and nitrates. Examples of complexes include ammine complexes, cyano complexes, halogeno complexes, and hydroxy complexes. The solvent for the metal deposition solution may be the same as those exemplified as the solvent for the seed particle generation solution described above. However, an aqueous solvent is preferably used to facilitate dissolution of the quinone oligomer.
[0032] The concentration of the quinone oligomer in the metal deposition solution is not particularly limited, but if the concentration is too low, the effect of the quinone oligomer may not be fully achieved. Therefore, the concentration of the quinone oligomer in the metal deposition solution is, for example, 0.02 g / L or more, preferably 0.05 g / L or more, 0.1 g / L or more, or 0.2 g / L or more. Furthermore, if the quinone oligomer concentration is too high, too many impurities will adhere to the deposited metal, making the process of removing these impurities complicated. Therefore, the concentration of the quinone oligomer in the metal deposition solution may be, for example, 200 g / L or less, 100 g / L or less, 50 g / L or less, 20 g / L or less, or 10 g / L or less.
[0033] The type of metal to be deposited is not particularly limited, but is preferably a metal that easily forms a complex with the quinone oligomer. For example, the metal is a transition metal (an element of Groups 3 to 11), more preferably a noble metal (Au, Ag, Pt, Pd, Rh, Ru, Ir, Os), and even more preferably a platinum group metal (Pt, Pd, Rh, Ru, Ir, Os).
[0034] By including a quinone oligomer in a metal deposition solution, coarsening of the metal deposited from the metal deposition solution can be suppressed. As a result, even when the metal is deposited on a substrate, aggregation and necking of the metal are suppressed. This is presumably because the quinone oligomer forms a complex with the dissolved metal, thereby favorably controlling the metal deposition behavior (e.g., reaction rate). The effect of such quinone oligomers is particularly pronounced when depositing platinum group elements. Note that the above speculation on the mechanism is not intended to limit the present technology in any way.
[0035] The metal deposition solution may contain a reducing agent. Examples of reducing agents that can be used include hydrazine compounds such as hydrazine carbonate, hydrazine, hydrazine hydrate, phenylhydrazine, hydrazine sulfate, hydrazine dihydrochloride, and alkylhydrazine. Other examples of reducing agents include organic acids such as tartaric acid, citric acid, and ascorbic acid, as well as their salts (tartrates, citrates, and ascorbates), and sodium borohydride. Among these, hydrazine carbonate, tartrates (e.g., sodium tartrate), and citrates (e.g., sodium citrate), which are not toxic and can form uniform, smooth-surfaced metal particles, are preferred. The reducing agent may be premixed with the metal deposition solution or may be added during the metal deposition process described below. The amount of reducing agent added is not particularly limited, as it can be appropriately determined based on the state of the reaction system.
[0036] The metal deposition solution may contain various additives, such as a protective agent, a dispersant, and a complexing agent.
[0037] Examples of ceramic particles that can be used as the substrate include alumina (Al2O3), silica (SiO2), zirconia (ZrO2), magnesia (MgO), titania (TiO2), ceria (CeO2), yttria (Y2O3), hafnia (HfO2), barium titanate (BaTiO3), manganese dioxide (MnO2), lime (CaO), zinc oxide (ZnO), red iron oxide (Fe2O3), zircon (ZrSiO4), and mullite (Al6O 13 The powder material may be an oxide ceramic such as silicon nitride (SiN), aluminum silicate, or a non-oxide ceramic such as silicon nitride (SiN), boron nitride (BN), aluminum nitride (AlN), silicon carbide (SiC), or boron carbonitride, or may be a composite material containing at least one of these ceramics. These ceramics may be used alone or in combination of two or more depending on the application of the powder material and the desired properties.
[0038] The average particle size of the ceramic particles is not particularly limited, but is, for example, 0.01 μm to 1 μm, preferably 0.05 μm to 0.8 μm, and more preferably 0.1 μm to 0.4 μm. The particle size here is the Z-average particle size (D) measured by analyzing using the cumulant method in dynamic light scattering (DLS). DLS The above average particle size range may be the same even when metal particles are used as the substrate instead of ceramic particles.
[0039] The ceramic particles preferably carry metal particles (hereinafter also referred to as "seed particles") containing a predetermined metal on a portion of their surface. Such seed particles are particles that serve as nuclei for particle growth. The presence of seed particles on the surfaces of the ceramic particles allows the metal to precipitate from the seed particles as starting points in the metal precipitation step described below, thereby enabling the metal to be efficiently attached to the surfaces of the ceramic particles.
[0040] The metal element constituting the seed particles may be an element of the same group (or even the same type) as the metal dissolved in the metal deposition solution, or a metal element of a different type, but is preferably an element of the same group. For example, it is preferable that the metal dissolved in the metal deposition solution and the seed particles are composed of platinum group elements.
[0041] The amount of seed particles supported may be, for example, 0.05 or less, 0.03 or less, 0.02 or less, or 0.01 or less, when the weight of the ceramic particles is 1. The amount of seed particles supported may be, for example, 0.002 or more, or 0.005 or more, when the weight of the ceramic particles is 1. If the amount of seed particles supported is too small, the amount of metal precipitated on the surfaces of the ceramic particles may be insufficient.
[0042] The method for preparing ceramic particles having seed particles supported on a portion of their surface is not particularly limited, but they can be prepared, for example, by a liquid-phase reduction method. In the liquid-phase reduction method, first, a solution in which a metal compound containing the metal element that constitutes the seed particles is dissolved (hereinafter also referred to as a "seed particle generating solution") is prepared. As the metal compound, salts, complexes, etc. of the target metal can be preferably used. Examples of salts include halides such as chlorides, bromides, and iodides, hydroxides, sulfides, sulfates, and nitrates. Examples of complexes include ammine complexes, cyano complexes, halogeno complexes, and hydroxy complexes.
[0043] The solvent for the seed particle generating solution may be either an aqueous solvent or an organic solvent. The aqueous solvent may be water (e.g., pure water, deionized water, etc.) or a mixed solution mainly composed of water (e.g., a mixed solution of water and a lower alcohol). In this specification, the term "mixed solution mainly composed of water" refers to a mixed solution in which 50 vol % or more of the mixed solution is water. The organic solvent may be alcohols such as methanol or ethanol, ketones such as acetone or methyl ketone, or esters such as ethyl acetate.
[0044] Next, the seed particle generating solution, ceramic particles, and a suitable reducing agent are mixed and reduced to generate seed particles on the surfaces of the ceramic particles. The reducing agent may be the same as those exemplified as reducing agents that may be contained in the metal deposition solution described above.
[0045] In order to prevent uneven distribution of seed particles formed on the ceramic particle surfaces, the reduction treatment is preferably carried out with stirring. Furthermore, it is preferable to disperse the ceramic particles in advance by ultrasonic dispersion or the like before mixing with the reducing agent.
[0046] The concentration of the metal compound to be reduced is not particularly limited, but the solution can be prepared to have a concentration of, for example, 0.001 mM to 1 mM (e.g., 0.01 mM to 0.1 mM). Various additives may also be added to the solution. Examples of such additives include protective agents, dispersants, and complexing agents.
[0047] The method for recovering the ceramic particles having the seed particles produced by the reduction treatment described above can be the same as conventional methods and is not particularly limited. For example, the ceramic particles are first precipitated in a liquid or centrifuged to remove the supernatant. After that, the ceramic particles are preferably washed multiple times and then dried to obtain ceramic particles having the seed particles supported on a portion of their surface. For example, an aqueous solvent or an organic solvent such as an alcohol can be used for washing.
[0048] In this manner, ceramic particles carrying seed particles on a portion of their surface can be prepared. The average particle size of the seed particles is not particularly limited, but can be, for example, 50 nm or less, 30 nm or less, 20 nm or less, or 10 nm or less. The lower limit of the average particle size of the seed particles is not limited, but can be, for example, 1 nm or more. The average particle size of the seed particles is measured as the arithmetic mean of the Feret diameter (horizontal) of 400 particles randomly selected from an SEM image.
[0049] (2) Metal precipitation process In the metal deposition step, metal is deposited from the metal deposition solution. When depositing metal on a substrate, the prepared substrate (ceramic particles supporting the seed particles in this embodiment) is mixed with the metal deposition solution, and metal is deposited on the substrate. Here, the metal is deposited by a liquid-phase reduction method. From the viewpoint of more uniform metal deposition, it is preferable to proceed with the reduction reaction while stirring. Although there are no particular restrictions, the reduction reaction time is preferably, for example, about 0.1 to 3 hours. From the same viewpoint, it is also preferable to mix the ceramic particles with the metal deposition solution without mixing a reducing agent, disperse the ceramic particles by ultrasonic dispersion or the like, and then mix in the reducing agent.
[0050] To facilitate the progress of the reduction treatment, it is preferable to add a pH adjuster to the mixed solution of the ceramic particles and the metal deposition solution to adjust the pH to 8 or higher, for example, about 9 to 11. Here, the pH adjuster may be, for example, sodium hydroxide (NaOH), aqueous ammonia, or other basic substances.
[0051] The recovery of the powder material containing the metal or metal-adhered substrate (ceramic particles) produced by the reduction treatment described above can be performed in the same manner as in the past, and is not particularly limited. In one example, the powder material is first precipitated in a liquid or centrifuged to remove the supernatant. The powder material is then preferably washed multiple times and then dried to obtain the powder material. For example, an aqueous solvent or an organic solvent such as alcohols can be used for washing.
[0052] The metal (precipitated metal) produced by the method disclosed herein may be, for example, in the form of particles or a film. When the precipitated metal is present in particulate form, its average particle diameter may be, for example, 1 nm or more, 10 nm or more, 20 nm or more, 30 nm or more, or 40 nm or more. Furthermore, the average particle diameter may be, for example, 100 nm or less, 90 nm or less, 80 nm or less, 70 nm or less, or 60 nm or less. In this specification, the average particle diameter of the precipitated metal refers to the arithmetic mean of the Feret diameter (horizontal) measured on 400 particles randomly sampled from an SEM image.
[0053] Organic matter derived from quinone oligomers can be observed on the surface of the generated metal. Such organic matter can contribute to suppressing necking and coarsening between metals. Such organic matter may be quinone oligomers with reduced solubility in water, or may be quinone oligomers that have been polymerized (e.g., quinone polymers) or gelled. Furthermore, such organic matter dissolves in alcohol and can be easily removed by washing. Furthermore, such organic matter can be thermally decomposed to produce, for example, hydroquinone, and further, benzoquinone and phenol. When such organic matter is analyzed by MALDI-TOF / MS, at least one peak can be detected at m / z values of 2000 or more, 4000 or more, 7000 or more, or 10000 or more.
[0054] The powder material containing metal produced by the above-described method (e.g., a powder material containing core-shell particles having ceramic particles or metal particles as a core and a precipitated metal as a shell) can be used in a variety of applications, such as the production of conductive members for electronic components and semiconductor devices.
[0055] Test examples relating to the present technology will be described below, but these test examples are not intended to limit the present technology.
[0056] <Synthesis of quinone oligomers> 15 g of hydroquinone was dissolved in 900 mL of pure water and oxidized and polymerized using oxygen gas under basic conditions, resulting in an aqueous solution containing quinone oligomers.
[0057] <Analysis of quinone oligomers (1)> Acetone was added to the aqueous solution containing the quinone oligomer obtained above to obtain a black precipitate, which was analyzed by pyrolysis GC-MS under the following conditions. Measurement conditions Equipment used: GC-MS-QR2010 Ultra (Shimadzu Corporation) Thermal decomposition conditions: Double shot: Thermal decomposition at 300°C, then again at 600°C Analysis software LabSolutions (Shimadzu Corporation)
[0058] The results of the pyrolysis GC-MS (pyrolysis temperature: 300°C) measurement are shown in Figure 1, and the results of the pyrolysis GC-MS (pyrolysis temperature: 600°C) measurement are shown in Figure 2. Furthermore, information on each peak (retention time (Ret. Time), peak area (Area), peak height (Height), peak area / peak height (A / H), concentration (ratio of each peak area to the total peak area), and substance name are shown in Tables 1 and 2. Furthermore, each substance was divided into categories 1 to 3 in order of the strongest correlation with the unique structure of quinone oligomers. Category 1 was hydroquinone or benzoquinone, which are the main skeleton of quinone oligomers; Category 2 was substances with a benzene ring presumed to be derived from quinone; and Category 3 was all other substances.
[0059] [Table 1]
[0060] [Table 2]
[0061] As shown in Tables 1 and 2, a large number of substances in Category 1 were detected, especially in the pyrolysis at 600°C. This is thought to be because the bonds of quinone oligomers were not sufficiently broken at 300°C, but many of them were broken at 600°C.
[0062] <Analysis of quinone oligomers (2)> The black precipitate obtained above was dissolved and suspended in water, and then subjected to MALDI-TOF / MS measurement under the following conditions. Measurement conditions Equipment used: JMS-S3000 (manufactured by JEOL) Ionization method LDI Measurement mode: Spiral TOF mode (high resolution mode) Ion polarity Negative Scan range m / z value 10~10000
[0063] The results of the MALDI-TOF / MS measurements are shown in Figures 3 and 4. Figure 3 shows the peaks in the m / z range (horizontal axis) of 10 to 1500. Figure 4 shows an enlarged view of the peaks in Figure 3 in the m / z range (horizontal axis) of 10 to 300. The vertical axes of Figures 3 and 4 represent absolute intensity. As shown in Figure 3, a group of peaks derived from the sample was detected in the m / z range of 10 to 1200. In this measurement, the black precipitate was dissolved and suspended in water as a pretreatment, and high peak intensities were obtained in negative mode, which detects anions. From this, it is presumed that the detected peaks are derived from substances that are easily anionized, i.e., have a structure with many OH groups. Furthermore, as shown in Figure 4, a large number of peaks were detected in succession in this measurement. Based on this peak detection trend, it is presumed that the sample is a polymer, with multiple components being generated and mixed.
[0064] <Analysis of quinone oligomers (3)> The concentration of the quinone oligomer solution was measured as follows. First, hydroquinone was dissolved in distilled water to prepare three hydroquinone standard solutions at 5, 10, and 20 g / L. GC-MS measurements were performed to create a calibration curve. Using this calibration curve, the concentration of unreacted hydroquinone in the quinone oligomer solution was measured, and the value subtracted from the concentration of hydroquinone in the initial amount was used to determine the quinone oligomer concentration. For these measurements, an Agilent 7010B Triple Quadrupole GC / MS (Agilent Technologies) was used, with a DB-WAX UI column, 30 m long, 0.32 mm internal diameter, and 0.25 μm film thickness.
[0065] [Test 1: Deposition of Pd on the surface of Ag particles] Example 1 A tetraamminepalladium (II) aqueous solution was prepared by mixing 15.9 g of dichlorodiaminepalladium (DDPd), 80 mL of pure water, and 14.4 mL of 28% aqueous ammonia. Pure water was added to the aqueous solution to make a constant volume of 200 mL, resulting in a Pd solution with a Pd concentration of 40 g / L. Next, 81.7 mL of pure water was added to 3 g of Ag powder (Mitsui Mining & Smelting Co., Ltd., SPQ-02X). While stirring (400 rpm) using a magnetic stirrer and a 40 mm rod-shaped stir bar, 10 mL of an aqueous solution containing 6 g / L quinone oligomer and 8.33 mL of the above Pd solution were added and stirring continued for 5 minutes (at this time, the weight ratio of Pd to the total of Ag and Pd was 10 wt%). After 10 minutes of ultrasonic dispersion using an ultrasonic cleaner, 0.85 mL of hydrazine carbonate was added while stirring under the same conditions. The solution temperature was 25–31°C, and foaming and blackening due to precipitation of Pd were observed after the addition of hydrazine carbonate. After stirring for 30 minutes, the resulting powder was allowed to settle for 1 hour and the supernatant was removed. A gel-like organic material derived from the quinone oligomer was found on the surface of the settled particles. This gel-like organic material is thought to be the result of further polymerization of the quinone oligomers, resulting in a higher molecular weight.
[0066] The precipitated powder was added to 40 mL of a pure water-ethanol mixture (volume ratio 1:1), crushed with a glass rod, and ultrasonically dispersed. The organic matter was then centrifuged at 6000 rpm for 5 minutes to settle the powder, and the supernatant was removed to wash the organic matter. This washing process was repeated three times. The precipitated powder was dried at 60°C for 18 hours and crushed in a mortar to obtain a powder material containing particles in which Pd had precipitated on Ag particles.
[0067] (Comparative Example 1) A powder material was obtained in the same manner as in Example 1, except that pure water was used instead of the aqueous solution containing the quinone oligomer.
[0068] <EDX analysis of powder materials> The powder material obtained in Example 1 was embedded in resin, then sliced using a focused ion beam (FIB), and subjected to TEM-EDX analysis. The powder material obtained in Comparative Example 1 was also subjected to FE-SEM-EDX analysis. FIG. 5 shows the results of the TEM-EDX analysis of the powder material in Example 1 (magnification: 100,000 times). FIG. 6 shows the results of the TEM-EDX analysis of the powder material in Example 1 (magnification: 1,000,000 times). FIG. 7 shows the results of the FE-SEM-EDX analysis of the powder material in Comparative Example 1 (magnification: 20,000 times).
[0069] <DLS measurement of powder materials> The powder material obtained in Example 1 was added to 40 mL of pure water and ultrasonically dispersed, followed by DLS (Dynamic Light Scavenging) measurement (Zetasizer nano, manufactured by Marlboro Panalytical). In the DLS measurement, the Z-average particle size and polydispersity index (PDI), which are measured by cumulant analysis, were measured. The same procedure was also performed on the powder material obtained in Comparative Example 1. DLS measurement was also performed on the Ag powder used as the raw material. The results are shown in Table 3.
[0070] [Table 3]
[0071] As shown in Figure 5, Pd is precipitated almost uniformly on the surface of the Ag particles in the powder material of Example 1, and it is found to have a core-shell structure. Furthermore, as shown in Figure 6, it was found that the shell portion (Pd) of the powder material of Example 1 is composed of roughly two layers of particles of about 5 nm stacked together, and the thickness of the shell portion is about 10 nm.
[0072] Furthermore, as shown in Table 3, the powder material in Example 1 had substantially the same Z-average particle size and PDI as the raw Ag powder, which indicates that the powder material in Example 1 suppressed necking between Pd particles formed on the surfaces of different Ag particles.
[0073] 7, Pd was precipitated almost uniformly on the surfaces of Ag particles in the powder material of Comparative Example 1. However, many secondary particles consisting of aggregated Ag particles were observed in the powder material of Comparative Example 1. This is thought to be due to necking between Pd precipitated on the surfaces of different Ag particles.
[0074] Furthermore, DLS measurement could not be performed on the powder material in Comparative Example 1 because the sample settled too quickly, which is thought to be because the powder material in Comparative Example 1 contains a large amount of secondary particles.
[0075] [Test 2: Deposition of Pt on the surface of Au particles] Example 2 2 g of gold powder (Au2061 L-82B) was mixed with 50 mL of water and 6 mL of an aqueous solution containing 6 g / L quinone oligomers. While stirring, 0.397 g of dichlorotetraammineplatinum(II) hydrate (Pt[(NH3)4]Cl2·H2O) (equivalent to 0.220 g of Pt) was added (the weight ratio of Pt to the total of Au and Pt was 10 wt%). The mixture was stirred for 5 minutes with a magnetic stirrer, then ultrasonically dispersed for 10 minutes while stirring with a glass rod. Then, 0.56 mL of hydrazine carbonate was added while stirring with a magnetic stirrer. Immediately, the slurry turned black due to platinum precipitation. After stirring for an additional 30 minutes, the powder was allowed to settle and the supernatant was removed. Organic matter derived from the quinone oligomers was found to adhere to the surfaces of the settled particles. The precipitated powder was washed with a pure water-ethanol mixture (volume ratio 1:1) in the same manner as in Example 1, then dried and lightly crushed in a mortar to obtain a powder material.
[0076] (Comparative Example 2) A powder material was obtained in the same manner as in Example 2, except that pure water was used instead of the aqueous solution containing the quinone oligomer.
[0077] The powder material obtained in Example 2 was analyzed by TEM-EDX in the same manner as in Example 1. FIG. 8 shows the results of the TEM-EDX analysis of the powder material in Example 2 (magnification: 100,000 times). FIG. 9 shows the results of the TEM-EDX analysis of the powder material in Example 2 (magnification: 1,000,000 times). The powder material obtained in Comparative Example 2 was also analyzed by FE-SEM-EDX. FIG. 10 shows the results of the FE-SEM-EDX analysis of the powder material in Comparative Example 2 (magnification: 20,000 times).
[0078] DLS measurement was performed on the powder material obtained in Example 2 in the same manner as in Example 1. The same procedure was also performed on the powder material obtained in Comparative Example 2. DLS measurement was also performed on the Au powder used as the raw material in the same manner. The results are shown in Table 4.
[0079] [Table 4]
[0080] As shown in Fig. 8, the powder material in Example 2 has a core-shell structure in which Pt is deposited almost uniformly on the surface of the Au particles. Also, as shown in Fig. 9, the shell portion (Pt) of the powder material in Example 2 is composed of multiple layers of particles of about 2 nm, and the thickness of the shell portion is about 20 nm.
[0081] Furthermore, as shown in Table 4, the powder material in Example 2 had substantially the same Z-average particle size and PDI as the raw Au powder. This indicates that the powder material in Example 2 suppressed necking between Pt particles formed on the surfaces of different Au particles.
[0082] 10, in the powder material of Comparative Example 2, Pt was precipitated almost uniformly on the surfaces of the Au particles. However, many secondary particles formed by aggregation of Au particles were observed in the powder material of Comparative Example 2. This is thought to be due to necking between Pt precipitated on the surfaces of different Au particles.
[0083] Furthermore, DLS measurement could not be performed on the powder material in Comparative Example 2 because the sample settled too quickly, which is thought to be because the powder material in Comparative Example 2 contained a large amount of secondary particles.
[0084] [Test 3: Deposition of Pd on the surface of alumina particles] Example 3 1.02 g of ammonium chloride was dissolved in 10 mL of pure water, and 0.835 g of palladium chloride (Pd: 0.501 g, 0.00471 mol) was added and dissolved therein. The solution was adjusted to a constant volume of 100 mL to prepare an aqueous solution of palladium ammonia complex. Next, 8 g of alumina powder was added to 2320 mL of pure water, ultrasonically dispersed, and stirred. 4 mL of the above palladium ammonia complex aqueous solution was added, and 80 mL of 0.12 mol / L hydrazine hydrate aqueous solution was added while stirring, and stirring was continued for another 30 minutes. This resulted in the preparation of alumina powder carrying Pd seed particles. At this time, the color of the slurry turned slightly brown due to the precipitation of Pd particles.
[0085] To 5.47 g of dichlorodiaminepalladium (DDPd), 82.5 mL of an aqueous solution containing 6 g / L of quinone oligomer, 4.95 mL of 28% aqueous ammonia, and 737 mL of pure water were added. The mixture was stirred with a magnetic stirrer and then treated in an ultrasonic cleaner for 5 minutes to dissolve the DDPd. 8.14 g of the Pd seed particle-supported alumina powder was added and stirred. The mixture was then ultrasonically dispersed for 10 minutes using an ultrasonic cleaner (the weight ratio of Pd to the total weight of alumina and Pd was 25 wt%). While stirring, 7.04 mL of a 70% aqueous hydrazine carbonate solution was added at 25°C. After approximately 5–6 minutes, foaming and blackening due to Pd precipitation were observed. After 30 minutes of stirring, the resulting powder was allowed to settle for 1 hour, the supernatant was removed, and the mixture was washed with ethanol using a centrifuge. This yielded the powder material described in Example 3.
[0086] Example 4 A powder material was obtained in the same manner as in Example 3, except that the amount of Pd seed particle-supporting alumina powder was 0.9 g. That is, the weight ratio of Pd to the total of alumina and Pd was 75 wt %.
[0087] (Comparative Example 3) A powder material was obtained in the same manner as in Example 3, except that pure water was used instead of the aqueous solution containing the quinone oligomer.
[0088] The powder materials obtained in Example 3, Example 4, and Comparative Example 3 were each observed by FE-SEM. FIG. 11 shows a backscattered electron image of the FE-SEM of the powder material in Example 3. FIG. 12 shows a backscattered electron image of the FE-SEM of the powder material in Example 4. FIG. 13 shows a backscattered electron image of the FE-SEM of the powder material in Comparative Example 3.
[0089] As shown in Figure 11, Pd was precipitated on the surface of alumina particles in the powder material of Example 3. Most of the precipitated Pd was in the form of particles, and adhered evenly to the surface of the alumina particles. The average particle diameter of the Pd particles was 0.05 µm. This average particle diameter refers to the arithmetic mean of the Feret diameter (horizontal) measured by randomly selecting 400 particles from the SEM image.
[0090] As shown in FIG. 12, it was confirmed that in the powder material of Example 4, compared to Example 3, Pd grew on the surface of the alumina particles, covering almost the entire surface of each alumina particle.
[0091] As shown in FIG. 13, in the powder material of Comparative Example 3, coarsening of Pd particles and necking between Pd particles were observed, and most of the Pd was not precipitated on the alumina particles.
[0092] The results of the above tests 1 to 3 show that necking between deposited metals can be suppressed by adding a quinone oligomer during liquid phase synthesis for depositing metals.
[0093] While specific examples of the present technology have been described in detail above based on test examples, these are merely examples and do not limit the scope of the claims. The technology described in the claims includes various modifications and alterations of the specific examples exemplified above.
Claims
1. An additive used in liquid phase synthesis for precipitating a metal from a solution containing a metal ion and / or a metal complex, the additive containing a quinone oligomer.
2. 2. The additive of claim 1, wherein the deposited metal is a transition metal.
3. The quinone oligomer has the following characteristics (1) and (2): (1) Hydroquinone is detected by pyrolysis GC-MS; (2) At least one peak is detected in the m / z range of 200 to 1200 by MALDI-TOF / MS; The additive according to claim 1 or 2, having
4. The additive according to claim 3, wherein, in a result of MALDI-TOF / MS measurement of the quinone oligomer, the sum of peak intensities in the m / z range of 200 to 1200 accounts for 50% or more of the total peak intensities.
5. A method for producing a metal, comprising precipitating the metal from a solution containing a metal ion and / or a metal complex and a quinone oligomer.
6. 6. The method for producing a metal according to claim 5, wherein the concentration of the quinone oligomer in the solution is 0.02 g / L or more and 200 g / L or less.
Citation Information
Patent Citations
Production of noble metal coated ceramic powder
JP1994087683A
Photochemical immobilization of ligands using quinones
JP1999505554A
Conductive particles and manufacturing method therefor
JP2010238419A
Core shell particle and use thereof
JP2020158864A
Silver-palladium alloy powder and use thereof
WO2020203076A1